Continuous supercritical route for quantum-confined GaN nanoparticles. Issue 2 (4th November 2015) - Giroire, B.; Marre, S.; Garcia, A.; Cardinal, T.; Aymonier, C.
Abstract : GaN quantum dots (QDs) are prepared in a one-step continuous process using anhydrous solvents at supercritical conditions (and temperatures below 450 °C) in short residence times, typically less than 25 s. Abstract : GaN quantum dots (QDs) are prepared in a one-step continuous process using anhydrous solvents at supercritical conditions (and temperatures below 450 °C) in short residence times, typically less than 25 s. The as-prepared QDs exhibit a strong luminescence in the ultraviolet ( λ max 350 nm) in agreement with the synthesis of quantum-confined GaN nanoparticles.